Sustainable Development Goals (SDGs) in Higher Education: Integrating Global Citizenship into the Curriculum - Naufal Izz; Syafiq Irfan (Proceeding of the International Conference on Global Education and Learning, 2024)
Higher education institutions play a critical role in advancing the Sustainable Development Goals (SDGs) by integrating global citizenship into the curriculum. This study examines the implementation of SDG-focused education, highlighting strategies for embedding global citizenship principles in higher education programs. Using a qualitative approach, data were collected through literature analysis and case studies from various universities. The findings indicate that interdisciplinary collaboration, experiential learning, and digital technology integration enhance students' awareness and engagement with global challenges. The study underscores the importance of institutional policies and educator training in fostering SDG-oriented education. These insights contribute to the development of comprehensive frameworks for embedding global citizenship in higher education curricula, promoting responsible and ethical leadership for sustainable development.